Finite element analysis of the three different posterior malleolus fixation strategies in relation to different fracture sizes. Issue 4 (April 2017) - Anwar, Adeel; Lv, Decheng; Zhao, Zhi; Zhang, Zhen; Lu, Ming; Nazir, Muhammad Umar; Qasim, Wasim
Abstract: Purpose: Appropriate fixation method for the posterior malleolar fractures (PMF) according to the fracture size is still not clear. Aim of this study was to evaluate the outcomes of the different fixation methods used for fixation of PMF by finite element analysis (FEA) and to compare the effect of fixation constructs on the size of the fracture computationally. Materials and methods: Three dimensional model of the tibia was reconstructed from computed tomography (CT) images. PMF of 30%, 40% and 50% fragment sizes were simulated through computational processing. Two antero-posterior (AP) lag screws, two postero-anterior (PA) lag screws and posterior buttress plate were analysed for three different fracture volumes. The simulated loads of 350 N and 700 N were applied to the proximal tibial end. Models were fixed distally in all degrees of freedom. Results: In single limb standing condition, the posterior plate group produced the lowest relative displacement (RD) among all the groups (0.01, 0.03 and 0.06 mm). Further nodal analysis of the highest RD fracture group showed a higher mean displacement of 4.77 mm and 4.23 mm in AP and PA lag screws model (p = 0.000). The amounts of stress subjected to these implants, 134.36 MPa and 140.75 MPa were also significantly lower (p = 0.000). There was a negative correlation (p = 0.021) between implant stress and the displacement which signifies a less stable fixation using AP and PA lag screws. Conclusion: Progressively increasing fracture size demands more stable fixation construct because RD increases significantly. Posterior buttress plate produces superior stability and lowest RD in PMF models irrespective of the fragment size.